Response to lethal UVA radiation in the Antarctic bacterium Pseudomonas extremaustralis: polyhydroxybutyrate and cold adaptation as protective factors - Tribelli, Paula Maria (2019)
Pseudomonas extremaustralis is an Antarctic bacterium with high stress resistance, able to grow under cold conditions. It is capable to produce polyhydroxyalkanoates (PHAs) mainly as polyhydroxybutyrate (PHB) and, to a lesser extent, medium-chain length polyhydroxyalkanoates (mclPHAs). In this work, we analyzed the role of PHAs and cold adaptation in the survival of P. extremaustralis after lethal UVA exposure. P. extremaustralis presented higher radiation resistance under polymer accumulation conditions. This result was also observed in the derivative mutant strain PHA−, deficient for mclPHAs production. On the contrary, the PHB− derivative mutant, deficient for PHB production, showed high sensitivity to UVA exposure. Complementation of the PHB− strain restored the wild-type resistance level, indicating that the UVA-sensitive phenotype is due to the lack of PHB. All strains exhibited high sensitivity to radiation when cultured under PHAs non-accumulation conditions. A slight decrease in PHB content was observed after UVA exposure in association with increased survival. The scattering of UVA radiation by intracellular PHAs granules could also result in bacterial cell protection. In addition, cold conditions improved UVA tolerance, probably depending on PHB mobilization. Results showed that PHB accumulation is crucial in the resistance to UVA in P. extremaustralis. Mechanisms involved probably entail depolymerization and light scattering acting as a screen, both conferring protection against oxidative stress.